IDENTIFIKASI SENYAWA FLAVONOID EKSTRAK KENTAL ETANOL DAUN SURUHAN (Peperomia Pellucida L.Kunth) DENGAN METODE KROMATOGRAFI KOLOM DAN KROMATOGRAFI LAPIS TIPIS - puspasari, heny; Puspita, Weni (Jurnal Komunitas Farmasi Nasional, 2023)
The leaves contain flavonoid compounds messengers. Flavonoid compounds secondary metabolite which is effective as an antioxidant, antibacterial and bitter taste. This research aims to find out whether or not there are compounds of flavonoids and flavonoid compounds types what is contained in the leaves of the Messenger (Peperomia Pellucida L. Kunth). Research done by maceration extraction using a solvent of ethanol 96%. Identification of flavonoid compound test done by phytochemicals shows telling leaf extract contains flavonoids. Identification of flavonoid done in Thin Layer Chromatography (TLC) to find a motion that gives the phase separation is good. After obtaining a good motion phase chromatography column done using phase of motion eluen of n-heksan: ethyl acetate: n-butanol (8:2:1) and Thin Layer Chromatography were tested using eluent n-butanol, acetic acid and water by comparison ( BAA) (4:1:5) to obtain the value of the Rf 92.85 and 94.28 indicating positive compounds of flavonoids from the isoflavones (Daidzein and Genistein).